2022
DOI: 10.1177/08919887221119979
|View full text |Cite
|
Sign up to set email alerts
|

Do Adult Attachment Style or Personality Mediate the Relationship Between Childhood Maltreatment and Late-Life Depression in Poor Communities?

Abstract: Objective Childhood maltreatment is associated with late-life depression. Preliminary evidence indicates that personality characteristics, in particular neuroticism and extroversion, and an anxious attachment style mediate this association. The objective is to evaluate 3 models, in which personality and attachment are considered mediators between childhood maltreatment and late-life depression in a socioeconomically disadvantaged Brazilian population. Methods This study included participants (n = 260) from soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…Hundreds of studies have shown that an individual's attachment pattern is a reliable predictor for explaining their differences in psychological dimensions, social dependencies, social cognition, romantic and marital relationships, stress and emotion control, reactions to separations, efficacy in interpersonal relationships, and individuals' schemas about themselves and others (Chen, 2023). The formation of insecure attachment styles (avoidant, anxious-ambivalent) leading to the acquisition of deviant identity bases (disorganized and premature) restricts their autonomy, increases their susceptibility to imitation, compliance, and seduction, thereby losing the decisiveness and clarity needed to reject irrational and socially unconventional demands (Jardim et al, 2022;Malek et al, 2022). Individuals with insecure attachment styles, due to their inability and inflexibility in adequately responding to adverse situations, will encounter behavioral and psychological problems (Guo & Ash, 2020;Huh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hundreds of studies have shown that an individual's attachment pattern is a reliable predictor for explaining their differences in psychological dimensions, social dependencies, social cognition, romantic and marital relationships, stress and emotion control, reactions to separations, efficacy in interpersonal relationships, and individuals' schemas about themselves and others (Chen, 2023). The formation of insecure attachment styles (avoidant, anxious-ambivalent) leading to the acquisition of deviant identity bases (disorganized and premature) restricts their autonomy, increases their susceptibility to imitation, compliance, and seduction, thereby losing the decisiveness and clarity needed to reject irrational and socially unconventional demands (Jardim et al, 2022;Malek et al, 2022). Individuals with insecure attachment styles, due to their inability and inflexibility in adequately responding to adverse situations, will encounter behavioral and psychological problems (Guo & Ash, 2020;Huh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Neurotics have low emotional stability, are worried, nervous, despondent, hopeless, stressed, shy, vulnerable, and impulsive. They generally have a negative attitude towards their work and living environment (Jardim et al, 2022). They react to their surroundings with higher emotional responses than the average person.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood trauma also moderates the effects of stressors experienced in adulthood, further increasing the chances that individuals will become depressed after experiencing stressful events (Colman et al, 2013). Attachment style may also play a role here, as attachment anxiety has been shown to mediate the relationship between childhood trauma and depression later in life (Gomes Jardim et al, 2023). Among those struggling with severe mental health challenges, PTSD was found to partially mediate the relationship between trauma and depression severity, such that those with severe PTSD had increased severity of depression as well (Subica et al, 2012).…”
Section: Tpmentioning
confidence: 99%